Conservative Treatment Without Any Intervention Compared With Other Therapeutic Strategies for Symptomatic Patent Ductus Arteriosus in Extremely Preterm Infants: A Nationwide Cohort Study in Korea - Shin, Jeonghee; Lee, Jin A; Oh, Sohee; Lee, Eun Hee; Choi, Byung Min (Frontiers in Pediatrics, 2021)
Abstract Objective: Although symptomatic treatment is the most preferred treatment strategy for proven symptomatic patent ductus arteriosus (PDA), a considerable number of infants only received conservative treatment without any pharmacological or surgical interventions in lower gestational age and lower birth weight group in Korea. We compared in-hospital outcomes of infants treated conservatively without any intervention and those of infants managed by other therapeutic strategies in extremely preterm infants with symptomatic PDA. Methods: A prospectively collected cohort study for 2,303 infants with gestational ages less than 28 weeks from Korean Neonatal Network database. These infants were classified into 4 groups according to the presence of PDA related symptoms and therapeutic treatment strategy: prophylactic treatment group, pre-symptomatic treatment (PST) group, symptomatic treatment (ST) group, and conservative treatment (CT) without any intervention group. Results: In multivariable logistic regression analysis, the risk of death was significantly decreased in PST group (Adjusted odds ratios [aOR] = 0.507; 95% confidence intervals [CI] 0.311-0.826) and ST group (aOR = 0.349; 95% CI 0.230-0.529) compared with CT group. However, the risk of composite outcome of severe bronchopulmonary dysplasia or death had not increased in PST group and ST group. Neonatal death due to pulmonary hemorrhage or neurological disease was significantly higher in CT group than in PST group or ST group. Conclusion: In extremely preterm infants, who are at highest risk of PDA related morbidities and mortality, even less interventional approach for PDA can be allowed, the rescued pharmacological or surgical interventions are necessary if they met for criteria for hemodynamically significant PDA.